Reminiscences of Past Days with Prof. Dr. Mohammad Ali Asgar, Fellow, BAS (Journal of Bangladesh Academy of Sciences, 2021)
Abstract not available.Journal of Bangladesh Academy of Sciences, Vol. 44, No. 2, iv-vii, 2020